3(x-2)=6x-(3x-6)

Simple and best practice solution for 3(x-2)=6x-(3x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)=6x-(3x-6) equation:



3(x-2)=6x-(3x-6)
We move all terms to the left:
3(x-2)-(6x-(3x-6))=0
We multiply parentheses
3x-(6x-(3x-6))-6=0
We calculate terms in parentheses: -(6x-(3x-6)), so:
6x-(3x-6)
We get rid of parentheses
6x-3x+6
We add all the numbers together, and all the variables
3x+6
Back to the equation:
-(3x+6)
We get rid of parentheses
3x-3x-6-6=0
We add all the numbers together, and all the variables
-12!=0
There is no solution for this equation

See similar equations:

| 5x+4(-6+3x)=1-x | | -3y-1/2(6y+4)=8y-4 | | 5x/5=-15/5 | | 5x+15-15=0-15 | | 60+0.70x=40+0.90 | | y+y(.2)=1280 | | 2.6(t-2)-6=9 | | X+2/3+7x-3/4=2 | | 1/6(18y+18)-7=-1/9(9y-36) | | x+x.2=1280 | | 7x-9-2x=x+2+x | | 5x2+26x-24=0 | | 3z+6=5 | | -6x+31=1 | | -3+x|5=-8 | | 3x+15/6=5x+5/6 | | -3+x/5=-1 | | 5/9y-4=36 | | x+4/12=1/6+x-1/7 | | x/2x-3=3/7 | | (6x-16)=(9x-4.5) | | 3=−2|(1/4)s−5|+3 | | 4x-7/5=4/3 | | 7x/9=5x/8+11 | | x/5x-3=5/26 | | 4(3w-6)=6(2w-4) | | 3=−2|1/4s−5|+3 | | x/5x-1=4/21 | | 4x/11=x/8+21 | | (50)(1+x)^10=200 | | 3z+5/4=-1 | | 2(x+8)=5x+5-3x+11 |

Equations solver categories